IMPLEMENTASI E-COMMERCE PADA PERCETAKAN BERBASIS WEB - Mansari Mansari (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2013)
Many ways that can be taken by the manufacturer in introducing its products, such as is by using the internet. Internet is the best facility to promote the exchange of information and product offerings. With the development of Internet, E-Commerce well developed, the electronic trading services which includes buying, selling, distributing, ordering goods and services through electronic systems. By using this internet consumers do not need to spend time to visit the location where the direct purchase of the product. Consumers can communicate directly with the manufacturer online and via email so that consumers can find product information that will be purchased. With the rapid development of e-commerce, the producers began to propagate the internet seriously because of the convenience and benefits or advantages offered quite a lot.Keyworld : E-Commerce, Manufacturer, Electronic Trading.